INFLUENCE OF FINANCIAL PERFORMANCE ON DIVIDEND POLICY: EVIDENCE IN BANKING COMPANIES ON THE INDONESIA STOCK EXCHANGE - Semara Putra, I Putu Mega Juli; Gunadi, I Gusti Ngurah Bagus (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Ngurah Rai, 2023)
This study aims to examine the effect of the variable capital adequacy ratio, debt-to-equity ratio, return on assets, and loan-to-deposit ratio on dividend policy. The study was carried out using a quantitative approach. The sample in this study was 12 banking companies listed on the Indonesia Stock Exchange for the 2019-2021 period. Determination of the sample using a purposive sampling method. The analytical tool used is Multiple Linear Regression Analysis. The results of this study indicate that the capital adequacy ratio variable has a negative effect on dividend policy, the debt-to-equity ratio has no effect on dividend policy, return on assets has a negative effect on dividend policy and loan to deposit ratio has no effect on dividend policy. This study implicates companies and policymakers in Ministries and Government Agencies in Indonesia to regulate the company's dividend policy on the Indonesian stock exchange so that it is mutually beneficial for companies and investors. This is the first study that examined dividend policy to influence financial performance in banking companies on the Indonesia stock exchange.